Design and fabrication of the ceramic composites via in-situ oxidized process: Phase and microstructure evolution in in-situ oxidized SiC/Al–Mg–Si process. Issue 1 (1st January 2023) - Jiao, Yuhong; Zhu, Jianfeng; Ge, Jinlong; Shi, Chunjie; Tai, Yanfang; Huang, Yicheng; Wang, Fen; Abdul, Waras
Abstract: The ceramic composites were designed through the regulation of the composition and temperature in the in-situ oxidized SiC/Al–Mg–Si composites process. The evolutions of the phase and microstructure were studied by X-ray Diffraction(XRD), Scanning Electron Microscope (SEM), and Transmission Electron Microscope(TEM) in different alloy addition and heating temperature. The products of in-situ oxidized SiC/Al–Mg–Si composites showed similar compositions due to high oxidation resistance on SiC since the heated temperature was below 1500 °C. Alloy addition dislodges the oxide shell on SiC. It promoted the oxidation of SiC, providing the sustained-release Si source to form the cordierite, mullite, and forsterite. Moissanite/spinel, mullite/spinel, and cordierite/spinel were obtained by controlling temperature or adding alloy. The mullite rods formed in 20% alloy addition samples at 1350 °C was detected. The step-like microstructure revealed that grains abide by a layer growth mechanism. The bending strength was enhanced from 13.83 ± 3.6 MPa to 22.32 ± 4.3 MPa by eutectic melting, which increased with the alloy addition and elevated temperature.